Meningkatkan Bahasa Anak Melalui APE di Kelompok B2 TK PAUD Terpadu Al-Madinah - Sri Mulianah; Asnar, Armi Nadilah; Tri Ayu Lestari (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
The purpose of writing this article is to see how the initial language is improved by using educational games (APE). Action Research in AL-MAIDNAH INTEGRATED PAUD Kindergarten. This research is based on consistency in planning the action itself, observing and reflecting on educational institutions. The subjects in this study were children of AL-MADINAH INTEGRATED PAUD Kindergarten who had problems with language skills. The method used is to use a non-text method, accompanied by documentation and also photo documentation. The results obtained. APE can improve your child's language skills in kindergarten. The application of APE language skills in schools can be influenced by factors such as teacher competence, school facilities and children. The synergistic effect on the elements of children's language skills increases optimally.